Air infiltration through building envelopes - Abi Shdid, Caesar (2011)
Air leakage through the building envelope into the building interiors has a considerable impact on the energy loads and consequently energy demand and energy costs of buildings. This phenomenon known as infiltration happens through various openings and venues in the building envelope varying from large openings such as doors and windows to minute cracks and crevices. In addition to impacting building energy loads, infiltration impacts indoor air quality and can result in moisture accumulation problems in the building envelope. A generalized review of infiltration that includes evaluation techniques and models, quantification, and interaction with other heat transfer phenomena is presented in this article.